Comparative residual effect of activated carbon and other organic amendments on immobilization and phytoavailability nickel and other metals to Egyptian Clover (Trifolium alexandrinum) in contaminated soil. Issue 7 (6th June 2020) - Sabir, Muhammad; Zia-Ur-Rehman, Muhammad; Aziz, Tariq; Raza Ahmad, Hamaad; Saifullah; Waraich, Ejaz Ahmad
Abstract: The effect of organic amendments on phytoavailability of nickel (Ni) and other metals in soil may change with time due to transformation of organic matter. We investigated the residual effect of organic amendments (farm manure [FM], poultry manure [PM], pressmud [PrM], and activated carbon [AC]) to immobilize Ni and other metals in soil and absorption of metals by Egyptian clover. Fresh and dry weights of Egyptian clover increased significantly ( p < 0.05) due to residual effect of amendments compared to control. Extractable Ni and other metals had significant positive correlation with residual organic matter in soil. Extractable manganese (Mn) in post-harvest soil of Egyptian clover increased compared with that of post-harvest soil of maize (previous crop). However, extractable copper (Cu) decreased with amendments. Copper was the maximum in control followed by AC. Zinc in soil decreased in FM and PrM treated pots but increased in pots amended with PM and AC. Concentration of Ni, Mn, and Cu was the minimum in shoots of those plants grown with AC amended pots compared to the control. It was concluded that AC was the most effective for immobilization of metals in soil which consequently decreased the concentration of metals in shoots of Egyptian clover.